Feasibility analysis for control of bioaerosol concentration at indoor corner via airflow from ventilation outlet with energy optimization - Zhang, Xingyu (2022)
An indoor corner may provide a relatively comfortable environment for bioaerosol growth and propagation, resulting in an increase in health risks for the resident. This paper presents a feasibility analysis for control of bioaerosol concentration at an indoor corner, defined as the area around ceiling edges, through airflow from ventilation outlet with optimized energy consumption. For the proposed approach, a gas-particle flow model with a chaotic moving vortex is developed to simulate the bioaerosol movement at an indoor corner via the Eulerian-Lagrangian method. In this model, the flowrate of the inlet fresh or air-conditioned air is tuned by a flowrate controller, which is installed at ventilation outlet or inside ventilation duct, in order to control the vortex trajectory. A residual concentration is defined as the ratio of the residual number of densely released particles at the corner to the area of the corner, in order to indicate the probability of bioaerosol movement, which is released sparsely and randomly by a microorganism in a real-world situation. The control strategies are then developed to optimize residual bioaerosol concentration and energy consumption by the orthogonal scheme. Based on the simulation results, a small variation of the airflow rate from the ventilation outlet contributes to reducing the residual concentration of bioaerosols that are originally released from the corner, or to increasing the residual concentration of detergents that are released from the ventilation outlet. It is thus concluded that a Pulse Width Modulation controller, with low amplitude, proper duty factor, period and time delay, is more energy efficient to improve the local indoor air quality.